Measurement for quality of services voice over internet protocol iTALK technology Telekom Malaysia Berhad / Norizan Mohd Hashim - Mohd Hashim, Norizan (2004)
Voices over IP applications allow telephone conversations over a standard Internet connection. This is an exciting new use of the Internet for most users, and can result in large cost savings for long distance toll calls. This is results a high growth rate in the use of these applications. Unfortunately due to the implementation of these applications, a large growth in voice traffic could seriously degrade the performance of Voice over IP [1]. This report outlines the progress this project has made in investigating these effects. This involved a large study of the ways of measuring network traffic. This report explains these issues and introduces some of the techniques currently being used to correct these problems. The project has focused on the use of two measurement system and this report goes on to detail the analysis of data from this system. Finally the purpose of this project is to create a measurement system via simulation to investigate the effects of VoIP on existing traffic and to measure the quality of service.